Early laboratory hematological parameters associated with COVID-19 mortality in an Amazonian population of Peru - Iglesias Osores, Sebastián (2023)
Background: COVID-19 has a significant impact on the hematopoietic system and hemostasis. Leukocytosis, lymphopenia, and thrombocytopenia are associated with increased severity and even death in COVID-19 cases. Objective: The aim is to examine the laboratory results of COVID-19 patients from a hospital in the Peruvian Amazon and their clinical prognosis. Material and Methods: An analytical cross-sectional study was carried out whose purpose was to identify the laboratory tests of patients with COVID-19 and mortality in a hospital in Ucayali, Peru during the period from March 13 to May 9, 2020, selecting a total of 127 with Covid-19. Mean and the standard deviation was described for age, leukocytes, neutrophils, platelets, RDW-SD; median and interquartile range for the variables lymphocyte, RN / L, fibrinogen, CRP, Ddimer, DHL, hematocrit, monocytes, eosinophils. Results: No differences were observed in this population regarding death and sex (OR: 1.31; 95% CI 0.92 to 1.87), however, it was observed that, for each one-year increase, the probability of death increased by 4% (PR: 1.04, 95% CI 1.03 to 1.05). The IRR (Incidence Risk Ratio) analysis for the numerical variables showed results strongly associated with hematological values such as Leukocytes (scaled by 2500 units) (IRR: 1.08, 95% CI 1.03 to 1.13), neutrophils (scaled by 2500 units) (IRR: 1.08; 95% CI 1.03 to 1.13), on the contrary, it is observed that the increase of 1000 units in lymphocytes, the probability of dying decreased by 48% (IRR: 0.52; 95% CI 0.38 to 071). Conclusions: Parameters such as leukocytes,neutrophils and D-dimer were statistically much higher in patients who died.